Comparing cone beam laminographic system trajectories for composite NDT. (November 2016) - O'Brien, Neil; Mavrogordato, Mark; Boardman, Richard; Sinclair, Ian; Hawker, Sam; Blumensath, Thomas
Abstract: We compare the quality of reconstruction obtainable using various laminographic system trajectories that have been described in the literature, with reference to detecting defects in composite materials in engineering. We start by describing a laminar phantom representing a simplified model of composite panel, which models certain defects that may arise in such materials, such as voids, resin rich areas, and delamination, and additionally features both blind and through holes along multiple axes. We simulate ideal cone-beam projections of this phantom with the different laminographic trajectories, applying both Simultaneous Iterative Reconstruction Technique (SIRT) and Conjugate Gradient Least Squares (CGLS) reconstruction algorithms. We compare the quality of the reconstructions with a view towards optimising the scan parameters for defect detectability in composite NDT applications.